STOCK REPURCHASE DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Nurul Safitri (2013)
This study aims to examine the existence of significant influence or otherwise of the variable Free Cash Flow, Price Earning Ratio and Leverage on Stock Repurchase on companies listed on the Stock Exchange in 2011. The population in this study are all companies listed on the Stock Exchange are doing Stock Repurchase in 2011. Data obtained from the published financial statements of the company. Obtained a total sample of 16 companies. The analysis technique used is multiple linear regression and hypothesis testing using the F test and t test with a confidence level of 5%. The results showed that Free Cash Flow is partially demonstrate significant value of 0.029 <0.05 (p value> 0.05), Price Earning Ratio partially showed insignificant value of 0.729> 0.05 (p value> 0.05), and leverage also showed significant results for 0.016 <0.05 (p value <0.05). The results achieved in this study is expected to be a material consideration for the company's progress and useful for writers as well as those reading this paper.